The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15386/cjmed-887
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Carcinoma - A Rare Case Report

Abstract: IntroductionThymic carcinoma is a rare, invasive mediastinal neoplasm with a tendency to metastasize. They constitute a heterogeneous group of tumors that present differently in terms of both behavior and prognosis.Case reportWe present a case of thymic carcinoma in a 55-year-old male patient known to suffer from Myasthenia gravis, whose chief complaints were fatigability, ptosis and coughing. All electromyography studies were done along with excision biopsy to reach the definitive diagnosis.Results and conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…There are limited data about the incidence of the small intestinal metastasis in patients with thymic carcinoma and the mechanism of distant metastasis from thymic carcinoma to small intestine remains unclear. Previous study suggested that extrathoracic metastases may occur because the tumor cells penetrated and spread from the great vessels in thymic carcinoma [ 2 ]. In our case, we indicated that hematogenous metastasis is the primary pathway leading to the metastasis of thymic carcinoma to the small intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data about the incidence of the small intestinal metastasis in patients with thymic carcinoma and the mechanism of distant metastasis from thymic carcinoma to small intestine remains unclear. Previous study suggested that extrathoracic metastases may occur because the tumor cells penetrated and spread from the great vessels in thymic carcinoma [ 2 ]. In our case, we indicated that hematogenous metastasis is the primary pathway leading to the metastasis of thymic carcinoma to the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Thymic carcinoma is a rare mediastinal neoplasm and has been reported to comprise only 0.06% of all thymic neoplasms [ 1 ]. Thymic carcinoma has a high malignant potential with a tendency to distant metastasis [ 2 ]. 80% of cases have local invasion of contiguous mediastinal structures, and 40% of cases present metastatic spread to bones, lung, pleura, liver, or lymph node [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rare, they nevertheless represent 20% of all mediastinal tumors and 50% of those located in the anterior mediastinum, with very few extrathoracic spread [1]. Thymic carcinoma is more aggressive than thymoma, and accounts for about 15% of the incidence of thymic tumors [2]. The most common histological types of thymic carcinoma are squamous cell carcinoma, lymphoepithelial carcinoma, undifferentiated carcinoma and so on.…”
Section: Introductionmentioning
confidence: 99%